Determine all polynomials P(x) with degree n≥1 and integer coefficients so that for every real number x the following condition is satisfied P(x)=(x−P(0))(x−P(1))(x−P(2))⋯(x−P(n−1))
Problem
Source:
Tags: algebra, polynomial, Ibero-American
15.09.2019 23:39
Nice problem. The only linear solution that works is P(x)=x, so from now and on assume degP≥2. We divide into two cases: If P(0)≠0 Take x=0, we have that P(0)=(−1)nP(0)P(1)…P(n−1)⟹P(1)P(2)…P(n−1)=(−1)n+1, which implies that all roots of P except P(0) are ±1. If one of the roots is 1 then P(1)=0 by taking x=1, which is a contradiction, hence all roots are −1, so we have that P(x)=(x+1)n−1(x−P(0)), then by taking x=1 we have that −1=P(1)=2n−1(1−P(0)) which is a clear contradiction since 2 does not divide 1. If P(0)=0 we have that P(x)=x(x−P(1))(x−P(2))…(x−P(n−1)), by taking x=1 we get (1−P(1))(1−P(2))…(1−P(n−1))=P(1)which is not true if 1−P(1) has a prime divisor because gcd. So, we have to check when P(1)=0 or P(1)=2, in the first case we have P(k)=1 for some 2\leq k \leq n-1, then we take x=k in the polynomial we have that 1=k^2(k-1)(k-P(2))\dots (k-P(n-1)) which is a contradiction. If P(1)=2 we have that (1-P(2))\dots (1-P(n-1))=-2, since 1 can't be root of this polynomial, we get that P(k)=3 for some k and P(i)=0 for all others, for n\geq 3 we get that P(x)=x^{n-2}(x-2)(x-3) which clearly doesn't satisfy the conditions, and hence no solutions exist except the identity.
16.09.2019 01:58
It's n\geq 1, so P(x)=x is a solution.
10.01.2022 18:23
Observe that if n\leq 2 then the only polynomial that works is P(x)=x. From now on, assume that n=\deg P\geq 3. For the sake of brevity, let r_i:=P(i)\in\mathbb{Z} for all 0\leq i\leq n-1. It follows that P(x)=(x-r_0)\cdots(x-r_{n-1}). By plugging in x=0 in the latter we get that r_0=P(0)=\prod_{i=0}^{n-1}(0-r_i)=r_0\cdot (-1)^n\cdot \prod_{i=1}^{n-1} r_i.Two cases arise, the first of which is r_0\neq 0. It follows from the latter that r_1,\ldots,r_{n-1}\in\{1,-1\} and furthermore, for some k\in\mathbb{N}, precisely n-2k of the r_i are equal to -1 and 2k-1 are equal to 1. In other words, P(x) rewrites as (x-r_0)(x-1)^{2k-1}(x+1)^{n-2k}. Since P(0)=r_0\neq 0, then 0 is not a root of P. However, P(1)=r_1 is a root of P by the problems's condition and since (x-1)^{2k-1}\neq(x-1)^0 divides P(x) it follows that r_1=0, contradiction! Now, assume that r_0=0. By plugging in x=k (for 1\leq k\leq n-1) in our polynomial we get that r_k=P(k)=\prod_{i=0}^{n-1}(k-r_i)=k (k-r_k)\cdot\prod_{i=1}^{k-1} (k-r_i)\prod_{i=k+1}^{n-1} (k-r_i).It follows that r_k=0 or, if not, k(k-r_k)\neq 0 divides r_k, which cannot happen unless k=1 or 2 in which case r_k=2 and r_k=4 respectively. Therefore, our polynomial looks like P(x)=x^{n-2}(x-r_1)(x-r_2) and r_1\in\{0,2\} and r_2\in\{0,4\}. These polynomials can easily be checked to not work, so the only answer is P(x)=x.
15.01.2022 18:16
Different finish: P(x)=x(x-P(1))(x-P(2))\dots (x-P(n-1)) \implies P(i)=0 or i(i-P(i))|P(i) \implies P(i) is even which implies contradiction because (1-P(1))(1-P(2))\dots (1-P(n-1))=P(1).
15.01.2022 18:50
XbenX wrote: If P(1)=2 we have that (1-P(2))\dots (1-P(n-1))=-2, since 1 can't be root of this polynomial, we get that P(k)=3 for some k and P(i)=0 for all others We have 1-P(k) | -2 \rightarrow P(k)=1 or P(k)=3. (Also, what if P(i)=1 and P(t)=2 for some i,t?) We should consider the previous cases separately. For case 1: P(k)=-1 \rightarrow -1=k(k+1)(k-2)(1-P(2))...(1-P(n-1)) \rightarrow k | -1 and since k>0 we have k=1, but then k+1 = 2 | -1, contradiction. For case 2: P(k)=3 \rightarrow 3=k(k-3)(k-2)(1-P(2))...(1-P(n-1)) \rightarrow k | 3 and since k>0 we have k=1 or k=3, and we end up in a contradiction similarly.
24.12.2022 08:51
Solution from Twitch Solves ISL: The answer is P(x) = x only. For n = 1 it's easy to check that P(x) = x is the only solution. We prove there are no others. Claim: If n > 1, any potential solution would need to have P(0)=0. Proof. If not, plug in x=0 and cancel P(0) to get 1 = (-1)^n P(1) P(2) \dots P(n-1). So we'd need to have P(k) = \pm1 for k=1,\dots,n-1. However, P(1) \neq 0, so actually P(k) = -1 for k=1,\dots,n-1. In other words P(x) = x(x+1)^{n-1}, which doesn't work for n \ge 2. \blacksquare We manually bash n=2 now: if P(x) = x^2 + bx then we'd need P(x) = x^2 + bx = (x-0)(x-(1+b)), which is impossible. Now assume n \ge 3. Claim: For k = 3, 4, \dots, n-1, any potential solution would have P(k) = 0. Proof. Note that by plugging in k, we get P(k) = k \cdot (k-P(k)) \cdot T_k for some integer T_k (namely T_k = \prod_{\substack{1 \le i \le n-1 \\ i \neq k}} (k-P(i)), but we don't need the actual value). This rearranges to (1+kT_k) P(k) = k^2T_k. However, 1 + kT_k shares no factors with k^2 T_k. So this can only occur if 1 + kT_k \in \{-1,1\} or T_k = 0. For k \ge 3, we extract P(k) = 0. \blacksquare Now, we are left with P(x) = x(x-P(1))(x-P(2)) x^{n-3}. So plug in x=1 and x=2: \begin{align*} P(1) &= (1-P(1)) (1-P(2)) \\ P(2) &= 2(2-P(1)) (2-P(2)) \cdot 2^{n-3}. \end{align*}Solve to get P(1) = \frac{2(2^n-2)}{2^n-8} and P(2) = \frac{3 \cdot 2^n}{2^n+4}. This means n \neq 3, and for n > 3 we have 2^n+4 \nmid 3 \cdot 2^n (since 2^n + 4 \nmid -12), so there are no other solutions.
04.03.2023 11:45
Looks like P(P(x))=0??? Hint please